Kemampuan Siswa Kelas X Farmasi Mempelajari Makhraj Huruf dan Ahkamul Huruf dalam Mata Pelajaran PAI di SMK Gema Nusantara Bukittinggi - Yendri Saputra; Supratman Zakir (Arden Jaya Publisher, 2021)
This research was conducted at SMK Gema Nusantara Bukittinggi with the aim of describing the ability of class X Pharmacy students in learning the makhraj letters and ahkamul letters in Islamic Education subjects using the CIPP model (Context, Input, Process, Product). The evaluation model used in this research is the CIPP (Context, Input, Process, Product) evaluation model. This evaluation model was developed by Daniel L. Stufflebeam et al. This type of research is evaluative research.The motivation of the writer to do this research is motivated by the phenomenon, from the results of the initial observations made by the writer saw that students were less able to learn the makhraj letters and ahkamul letters, it was proven that when students read the arguments in the PAI subject, the students were not able to understand the proper grouping of ahkamul letters. Based on the description above, it seems that students have difficulty in learning. To answer the above problems, the authors conducted field research (field research) using the CIPP model evaluation approach (Context, Input, Process, Product). The researcher intends to collect data on the evaluation of the CIPP model of the learning program for learning makhraj letters and ahkamul hururf in PAI subjects. The samples in this study were PAI teachers and class X pharmacy students of SMK Gema Nusantara Bukittinggi. The research instrument used observation guidelines and interview guidelines. Data collection techniques used are through observation, interviews and documentation. After the data is collected, the writer analyzes the data by selecting all the data obtained from several sources, then making data reduction, data presentation and drawing conclusions. From the results of the research that the authors do, the lack of students' ability to study letter makhraj and ahkamul letter in PAI subjects is because students do not have an interest in learning makhraj hururf and ahkamul letter and there is no support from the family to actively study religion, many students are lazy in repeat the subject matter. Then students are less able to classify the letters ahkamul (laws of tajwid) in the PAI material because students do not pay attention to the teacher explaining the material about letter makhraj and letter ahkamul in PAI subjects.